ANALISIS SEDIMEN PADA MODEL PENAHAN SEDIMEN TERBUKA DAN TERTUTUP - Diky, Diky Wahyudi (Jurnal Teknik Sipil : Rancang Bangun, 2024)
Sediment is material or fragments of rocks, minerals and organic materials that are carried away and move in the direction of river water flow. Sediment can be divided into base load (bead load) and suspended load. The bottom load moves in a rolling, sliding and jumping manner over the surface of the river bed. In optimizing river function, it is necessary to construct sediment control buildings to reduce sedimentation that occurs along the river. This research aims to determine the volume of open and closed type sediment storage and to compare open and closed type sediment storage. The methods that will be used in this research to determine the volume of sediment are stream flow, flow characteristics (Froude and Reynolds numbers) and sediment volume. The results of the research will show how large the sediment storage volume is for the two forms of sediment storage, for the closed type sediment storage the sediment storage volume is = 0.004898 m³. greater than the volume of open sediment storage (slit), namely (V) = 0.004683 m³ and for the comparison of open and closed sediment storage, the most effective in holding sediment is the closed type sediment storage which has a capacity = 93.1% greater than the storage volume open type (slit) = 72.1%.